Concentrations and isotopic analysis for the sources and transfer of lead in an urban atmosphere-plant-soil system. (1st June 2022) - Cong, Ling; Zhou, Shijun; Niyogi, Dev; Wu, Yanan; Yan, Guoxin; Dai, Liyi; Liu, Songyang; Zhang, Zhenming; Hu, Yuanhui
Abstract: Lead pollution has attracted significant attention over the years. However, research on the transfer of lead between urban atmospheric particles, soils, and plants remains rare. We measured lead concentrations and lead isotope ratios in total suspended particles (TSP), soil, and plants in an urban wetland in Beijing. The study period was September 2016–August 2017- covering all four seasons. The concentrations of lead in the atmospheric particles vary from 3.13 to 6.68 mg/m 3 . It is significantly higher in autumn than that in spring and summer ( P  < 0.05). There is also a significant difference between summer and winter ( P  < 0.05). The soil lead concentrations range from 57 to 114 mg/kg, with the highest concentration in spring, followed by summer, winter and autumn. The lead concentrations are 1.28–7.75 mg/kg in plants. The concentration was highest in spring and significantly higher than in summer. The bioaccumulation factor of Phragmites australis was 0.064 (<0.1), indicating that lead is not easily transferred to plants. Unlike the bioaccumulation factors, translocation factors have much higher values, indicating a higher transfer within the plants. Results also indicate an interesting seasonal pattern with almost 97% of lead in plants during spring being of atmospheric origin, whereas in autumn, soilborne sources contribute almost 94%. The isotopic compositions of lead in the urban atmosphere-soil-plant system show that lead pollution results from the mixing of geogenic and anthropogenic materials. Vehicle exhaust, crustal rocks and ore deposits are likely primary sources of lead pollution within the study domain. Graphical abstract: Image 1 Highlights: Lead concentrations in soils are much higher than that in TSP and plant samples. Contributions of airborne sources of lead vary from 6.5% to 97.3% in four seasons. Contributions of soilborne sources of lead vary from 2.7% to 93.5% in four seasons. Vehicle exhaust, crustal rocks and ore deposits are the main sources of lead pollution in Cuihu wetland in Beijing.